Penerapan Gerakan Literasi Sekolah Dalam Pembelajaran Pendidikan Agama Islam (PAI) Siswa Sdn 10 Sapiran Kota Bukittinggi - Pratama, Hernan; D, Deswalantri; J, Junaidi; N, Nurhasnah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The lack of understanding among some students at SDN 10 Sapiran in Bukittinggi city about the cultivation of the literacy movement - especially related to Islamic Religious Education literacy - is the impetus for this research. In addition, only a small number of students use their break time to read books, even though the school has a Reading Corner both in the library and in their respective classes. Instead, students spend their break time playing rather than learning to read Islamic Religious Education enrichment materials in the library. In this study the author used qualitative descriptive techniques. Documentation, interview, and observation were used to collect data. To perform data analysis techniques, explanatory data must be analysed or broken down. Data and information should then be linked to theories and concepts that support related discussions. This explanation should be based on qualitative methods, and conclusions should be drawn from the research problems. The findings of this study show that the literacy process in the School Literacy Movement (GSL) requires mastery of four indicators: reading, listening, writing and transmitting. In the reading activity stage, teachers and students use independent reading techniques by reading the contents of Asmaul Husna from student pack books and other reference books at home. At school, they continue the reading activity by reading the Asmaul Husna material aloud. The second step is listening, where the instructor and students listen to each other, the teacher explains things in front of the class, and students ask questions and the teacher responds.